Portraits of the Artist as a Young Wife: May Alcott Nieriker’s Influence on her Sister’s Literary Sketches, Fragments, and Narratives - Azelina Flint (European Journal of American Studies)
Throughout their adult lives Louisa May Alcott and her sister, May Alcott Nieriker, debated whether the female artist could combine an artistic career with marriage. For Louisa, marriage was a useful plot device in domestic fiction, but it could undermine the female artist’s productivity in reality. Contrastingly, May viewed marriage as enhancing her artistic outputs. This article surveys Louisa’s assessment of her sister’s ideas of romantic love across four fictional narratives that feature a heroine based on May, alongside May’s correspondence on her married life, contrasting the sisters’ philosophies on the complementarity of female artistry and romantic love.